2010
DOI: 10.1016/j.mcn.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of axonal trafficking of cytochrome c oxidase IV mRNA

Abstract: Trafficking and local translation of axonal mRNAs play a critical role in the development and function of this neuronal subcellular structural domain. In this report, we studied cytochrome c oxidase subunit IV (COXIV) mRNA trafficking into distal axons of primary superior cervical ganglia (SCG) neurons, and provide evidence that axonal trafficking and mitochondrial association of the mRNA is mediated by an element located in a 38 bp-long, hairpin-loop forming region within the 3’UTR of the transcript. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 36 publications
1
73
0
Order By: Relevance
“…These data are consistent with a critical role played by hairpin stem-loop secondary structures in mediating RNA trafficking (Chartrand et al 1999;Jambhekar and DeRisi 2007;Aschrafi et al 2010;Meer et al 2012).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These data are consistent with a critical role played by hairpin stem-loop secondary structures in mediating RNA trafficking (Chartrand et al 1999;Jambhekar and DeRisi 2007;Aschrafi et al 2010;Meer et al 2012).…”
Section: Discussionsupporting
confidence: 85%
“…The 3 ′ UTR of TH mRNA mediates reporter mRNA trafficking to axons mRNA trafficking and localization have been shown to be directed by cis-acting elements often found in the 3 ′ UTR of the mRNA (Martin and Zukin 2006;Jambhekar and DeRisi 2007;Aschrafi et al 2010). Comparative sequence analysis of the 3 ′ UTR of TH revealed that there are several evolutionary conserved regions that may contain regulatory elements (Fig.…”
Section: Local Synthesis Of Th Facilitates Axonal Dopamine Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data show that axons isolated from embryonic and adult rat DRG neurons are enriched in protein synthesis, mitochondrial, and neurite growth-related mRNAs that appear to be common critical elements found in other types of axons (Chun et al 1995(Chun et al , 1997Bassell et al 1998;Eng et al 1999;Zheng et al 2001;Gioio et al 2004;Willis et al 2005Willis et al , 2007Wu et al 2005;Leung et al 2006;Aschrafi et al 2008Aschrafi et al , 2010Taylor et al 2009;Andreassi et al 2010). …”
Section: The Repertoire Of Axonal Mrnas Changes Between Embryonic Andmentioning
confidence: 67%
“…Localisation elements mediating the subcellular distribution of mRNAs are commonly found within 3' UTRs (Andreassi et al, 2010;Aschrafi et al, 2010;Brittis et al, 2002;Kislauskis et al, 1994;Mili et al, 2008;Wu et al, 2005). In fact, the 3' UTR of the mouse RAB13 orthologue has been shown to localise transcripts to protrusion of mouse fibroblasts (Mili et al, 2008) using the MS2 system developed by the Singer lab (Bertrand et al, 1998), but the specific "zipcode" sequence responsible is unknown.…”
Section: Identification Of a Rab13 Mrna Zipcode Sequence That Localismentioning
confidence: 99%